“Grammar-translation” method, a linguistic historic err or of perspective: origins, dynamics and inconsistencies (2013)
The Grammar-Translation method is frequently referred to as the traditional ineffective approach par excellence. Such view is often justified by the claim that before the Audiolingual method oral performance in foreign language was not reached, and language classes were reduced to memorizing grammar rules and lists of vocabulary. Nevertheless, this opinion is derived from unproved claims, mainly made by misinformed authors for they offer no compelling empirical evidence to validate their restrictive descriptions where translation is shown as an invalid metacognitive strategy. The aim of this paper is to demonstrate that Grammar-Translation is merely an arbitrary historic label, developed by methodologists and theoreticians to encompass the history of language teaching from 1790 through 1950. References to Grammar-Translation are critically reviewed to make evident they are biased inferences based on partial evidence to account for the existence of any such methodology. The assumption that Grammar-Translation did exist, and that it is the negative model of teaching practices that should be better avoided at all costs, might reflect an unconstructive and unfounded ideological interest of mainstream theoreticians and unsuspecting teachers.